Fiscal Capacity Dilemma and Institutional Challenges of BAPELITBANGDA in the Development of Underdeveloped Regions in East Manggarai Regency - Fransiskus De Sales Mujur; Eri Yusnita Arvianti; Cahyo Sasmito (Universitas Tribhuwana Tungga Dewi, 2026)
Regional development disparities underscore the importance of policy implementation effectiveness, particularly following institutional reorganizations in planning agencies. Conducted from December 2024 to January 2025, this descriptive qualitative study aims to analyze the implementation of the Accelerated Development Program for Underdeveloped Regions (PPDT) in East Manggarai Regency using Van Meter and Van Horn's (1975) framework. Data were collected through in-depth interviews with BAPELITBANGDA officials, planning staff, village heads, and community representatives, supplemented by observation and document analysis. The findings reveal that PPDT implementation remains suboptimal due to an implementation gap between high-quality planning coordination at BAPELITBANGDA and low operational execution capacity at the technical field level. Road infrastructure, along with health and education indicators, has yet to meet macro targets. Supporting factors include harmonious inter-organizational coordination and public participation, whereas structural barriers are dominated by fiscal resource constraints, cutbacks in technical field personnel, and geographical challenges. This study recommends strengthening technical human resource capacity, optimizing budget execution, and repositioning BAPELITBANGDA as an evidence-based policy innovation center.Ketimpangan pembangunan daerah tertinggal menegaskan pentingnya efektivitas implementasi kebijakan, khususnya pasca-reorganisasi kelembagaan perencanaan daerah. Penelitian kualitatif-deskriptif yang dilaksanakan pada Desember 2024 hingga Januari 2025 ini bertujuan menganalisis implementasi Program Percepatan Pembangunan Daerah Tertinggal (PPDT) di Kabupaten Manggarai Timur berbasis kerangka Van Meter dan Van Horn (1975). Data dikumpulkan melalui wawancara mendalam dengan pimpinan BAPELITBANGDA, aparatur perencana, kepala desa, dan perwakilan masyarakat, serta ditunjang observasi dan studi dokumen. Hasil penelitian menunjukkan bahwa implementasi PPDT belum berjalan optimal akibat kesenjangan (implementation gap) antara tingginya kualitas koordinasi perencanaan di BAPELITBANGDA dan rendahnya kapasitas eksekusi operasional di tingkat teknis. Pembangunan infrastruktur jalan serta indikator kesehatan dan pendidikan belum mencapai target makro daerah. Faktor pendukung utama mencakup harmonisasi koordinasi inter-organisasional dan partisipasi publik. Sebaliknya, hambatan struktural didominasi oleh krisis sumber daya fiskal, pengurangan tenaga kerja teknis lapangan, dan kendala geografis. Penelitian ini merekomendasikan penataan kapasitas SDM teknis, efektivitas eksekusi anggaran, dan reposisi BAPELITBANGDA sebagai pusat inovasi kebijakan berbasis bukti empiris.